Miserable victims or Troublesome delinquents? A Critical perspective on the news media coverage of Chinese rural left-behind children - Ruixia Sun; Wei Han (Social Sciences and Humanities Open)
The fast urban development in China has attracted many migrant workers in rural areas heading for cities due to more job opportunities and higher salaries. Yet the succeeding population shift has created the group of left-behind children who often appear in headlines of news reports. This paper discusses the media representations of rural Chinese left-behind children in China Daily, a leading English newspaper in China, and analyzes the strategies the newspaper has employed to construct the images of left-behind children. We collected 110 news reports published in China Daily during 2004–2023 and sorted the data out with the software Nvivo 11. We employed the discourse-historical approach and the concept of agency to analyze the data and found that China Daily has constructed three major images of LBC: victims, problem-plagued group, beneficiaries. We found that, by illustration of LBC's vulnerability, China Daily draws support and help from the public to relieve LBC of predicament. Meanwhile the newspaper fulfils its duty as a leading official paper by advocating the endeavors the Chinese government has made in the description of LBC as beneficiaries, displaying a people-oriented government in the international community. The study contributes to the understanding of LBC in media portrayal and also demonstrates the impact of media in aiding the disadvantaged group and promoting the government's endeavors.